2023
DOI: 10.1186/s12889-023-16407-y
|View full text |Cite
|
Sign up to set email alerts
|

Burden of early-onset colorectal cancer along with attributable risk factors from 1990 to 2019: a comparative study between China and other G20 countries

Quanhui Li,
Miao Yu,
Haiguang Lv
et al.

Abstract: Purpose The credible data about the burden of early-onset colorectal cancer (EOCRC) in China when compared to other countries in the group of twenty (G20) remained unavailable. We aimed to assess the burden and trends of EOCRC and attributable risk factors in China. Meanwhile, the comparison in the burden and attributable risk factors between China and other G20 countries was also evaluated. Methods Data on the incidence, prevalence, mortality, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…However, it is important to note that risk factors for early‐onset CRC have been well‐studied, including increasing age, higher BMI or obesity, and family history of cancer. 13 Our study aligns with these findings, extends them by providing predictive models for future trends, and underscores the urgent need for interventions targeting these modifiable risk factors, as highlighted in existing literature.…”
Section: Discussionsupporting
confidence: 81%
“…However, it is important to note that risk factors for early‐onset CRC have been well‐studied, including increasing age, higher BMI or obesity, and family history of cancer. 13 Our study aligns with these findings, extends them by providing predictive models for future trends, and underscores the urgent need for interventions targeting these modifiable risk factors, as highlighted in existing literature.…”
Section: Discussionsupporting
confidence: 81%
“…Several American guidelines, including the American Cancer Society (ACS) [25], National Comprehensive Cancer Network (NCCN) [26], American College of Gastroenterology (ACG) [27] and the US preventative task force now recommend starting screening of average risk individuals at 45 years of age [28,29]. While there is no direct evidence that screening below the age of 50 years will reduce EOCRC, countries such as Italy, Austria and Japan have been screening patients in their 40's since the 1980s [24], and they are some of the few countries internationally where EOCRC rates have been declining [3,17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 28 ] studied the epidemiologic and clinical parameters and risk factors of Chinese patients with early-CRC and compared the results with counterparts from the G20 countries. The results showed that between 1990 and 2019, the age-standardized incidence rate and age-standardized prevalence rate of early-CRC in China increased (estimated annual percentage change 4.61 and 5.82).…”
Section: Epidemiologymentioning
confidence: 99%
“…The main risk factors for both sexes in Chinese patients in 2019 were a diet low in milk and calcium, drinking alcohol, smoking, and a diet high in red meat. It is estimated that during the next 10 years the age-standardized incidence rate, the age-standardized mortality rate, and the age-standardized rate of disability-adjusted life years will continuously increase in both sexes[ 28 ].…”
Section: Epidemiologymentioning
confidence: 99%